The effectiveness of aloe vera gel in reducing the pain of perineal wound - Dewi, Putri Sitronela; Hani, Umu; Anwar, Mochamad (MEDISAINS, 2020)
Background: Researches on applying ice gel and aloe vera gel compress to reduce perineal wound pain scale after childbirth has been widely studied and proven effective. However,  the effectiveness of using both has not been studied.Objective: The purpose of this study was to determine the effectiveness differences of ice gel and aloe vera gel in reducing the intensity of perineal wound pain.Methods: It applied a quasi-experimental research design. The population was 116 post-partum mothers, a sample of 56 mothers with sutured perineal wounds grade II, divided into two groups of intervention (aloe vera gel compress) and control (ice gel compress), with a consecutive sampling technique. The pain before and after the intervention was observed and analyzed using the Wilcoxon and Maan Whitney tests.Result: The mean reduction in pain scale in the group with the aloe vera gel treatment was more than that in another group with ice gel treatment, with a mean difference of 2.46 and 1.61. The statistical analysis results showed a significant difference in pain relief between the two groups, p<0.05.Conclusion: The aloe vera gel compresses are more effective than the ice gel compresses in reducing the scale of perineal pain after childbirth.